(Un)married with children? Exploring marriage between parities in Hong Kong. Issue 3 (2nd September 2022) - Gietel-Basten, Stuart A.; Verropoulou, Georgia
ABSTRACT: Births outside of marriage are comparatively rare in East Asia, but numbers appear to be rising. Such fertility tends to be concentrated among lower educational and socioeconomic groups which can entrench pre-existing inequalities in systems where such 'non-traditional' family forms are penalised. Most research in this area, however, has focused on the relationship between marriage and first birth. Using a large microdataset from Hong Kong, we explore the relationship between marriage and childbearing across the life-course. In particular, we examine the frequency of marriage between parities, and the various predictors of marrying (or not). Rather than 'life-long' cohabiters, we find roughly half of all couples who have a first birth outside of marriage do, in fact, marry before having their second child. The study concludes with some exploratory reasons for the apparently strong continuation of the relationship between marriage and childbearing in Hong Kong and in East Asia more generally.